Measuring Sense of Community Responsibility in Community‐Based Prevention Coalitions: An Item Response Theory Analysis. Issue 1 (14th September 2018) - Treitler, Peter C.; Andrew Peterson, N.; Howell, Tyriesa Howard; Powell, Kristen Gilmore
Abstract: Research on sense of community (SOC) has traditionally been approached from a resource perspective. Recently, however, research on the experience of SOC has evolved to include a related but distinct construct of sense of community responsibility (SOC‐R), or feelings of accountability for the well‐being of a community. This study applied item response theory to examine the psychometric properties of a SOC‐R scale used in an evaluation of community‐based substance abuse prevention coalitions. Data were collected in 2017 from coalition members (analytic sample = 309) in the northeastern United States. Findings indicate that the scale was reliable, unidimensional, and functioned well, particularly at low and moderate levels of the construct. The addition of two items intended to capture higher levels of the construct improved the scale's functioning at higher levels of SOC‐R. The adapted SOC‐R scale was also shown to have moderately strong relationships with conceptually relevant variables, including SOC, coalition participation, number of roles performed in the coalition, and engagement in community action activities. These findings provide empirical evidence to support the reliability and validity of the SOC‐R scale, and have critical implications for our conceptualization of the SOC construct, its measurement, and for the evaluation of community‐based prevention interventions. Highlights: Item response theory was applied to evaluate a sense of community responsibility (SOC‐R) scale. New items improved the scale's functioning at higher levels of SOC‐R. Findings support conceptualization of sense of community as a responsibility as well as a resource.